Moving to Their Own Beat: Exploring How Students Use Web 2.0 Technologies to Support Group Work outside of Class Time - Vaughan, Norman; Nickle, Todd; Silovs, Jim; Zimmer, Jim (Journal of interactive online learning, 2011)
Over the years, researchers have consistently reported that, regardless of the subject matter, students working in small groups tend to learn more of what is taught and retain it longer than when the same content is presented in other instructional formats (Beckman, 1990; Chickering & Gamson, 1991). The majority of these research studies have focused on cooperative learning techniques in the classroom, but there are few studies that have investigated the impact of group work and peer instruction on student learning outside of the classroom. A similar trend appears to exist with regards to student use of technology. There are a number of studies that have explored student use of technology in the classroom (Barnett, 2006; Graham, Tripp, Seawright & Joeckel, 2007; Hoekstra, 2008), but not many document how students are using technology to support learning beyond the classroom. The purpose of this research study was to address these gaps in the literature: How do students use Web 2.0 technologies to support group work outside of class time? (Contains 6 tables.)